2019
DOI: 10.1186/s12301-019-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

Stone-free rate after semirigid ureteroscopy with holmium laser lithotripsy versus laparoscopic ureterolithotomy for upper ureteral calculi: a multicenter study

Abstract: Background: Different treatment options were used to treat upper ureteral calculi. The aim of our study is to compare the stone-free rate and postoperative outcomes between semirigid ureteroscope with holmium laser lithotripsy and laparoscopic ureterolithotomy for the management of large solitary upper ureteral stones. Sixty-seven patients with a solitary upper ureteral stone who had LU or semirigid ureteroscopy in the period between January 2014 and March 2017 were included in our study. Out of the sixty-seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
7
0
2
Order By: Relevance
“…Pain abdomen was the presenting complaint in a study done in India by Jagannath et al 9 In contrast to these, Jeevaraman et al 15 found hematuria as the most common clinical presentation of ureteric calculi. In our study, left ureteric calculus (49.2%) was more common which was similar to study done by Rashid et al 16 and Ali et al 17 Right ureteric calculi undergoing laser lithotripsy was slightly more common (60.7%, 50.3% and 51.4%) in studies done by Jagannath et al, 9 Abedi et al 4 and Koju et al 3 respectively. Bilateral calculi were only 7.6% in our study and this finding was similar to other studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Pain abdomen was the presenting complaint in a study done in India by Jagannath et al 9 In contrast to these, Jeevaraman et al 15 found hematuria as the most common clinical presentation of ureteric calculi. In our study, left ureteric calculus (49.2%) was more common which was similar to study done by Rashid et al 16 and Ali et al 17 Right ureteric calculi undergoing laser lithotripsy was slightly more common (60.7%, 50.3% and 51.4%) in studies done by Jagannath et al, 9 Abedi et al 4 and Koju et al 3 respectively. Bilateral calculi were only 7.6% in our study and this finding was similar to other studies.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies show variation in the size of the calculus undergoing laser lithotripsy, the mean stone size ranging from 7.08 ± 1.66 mm to 14.44 ± 3.56 mm. 4,14,[16][17][18][19] Stone density also predict stone composition and different stones have different HU but success does not correlate with stone density. 20 The mean density of the calculus in our study was 1312.36 ± 324.37 and 87.3% patients had calculus with density ≥1000 HU.…”
Section: Subedi Et Almentioning
confidence: 99%
“…This definition is similar to that used in previous studies. 7,8 The urologists were blinded to each other's clinical assessment and the application of intravenous hydration during the SWL.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment success was defined as either complete freedom from lithiases or persistence of a residual stone <0.4 cm in diameter upon follow‐up plain abdominal radiography in the fourth week, after assessment by two individual urologists. This definition is similar to that used in previous studies 7,8 . The urologists were blinded to each other’s clinical assessment and the application of intravenous hydration during the SWL.…”
Section: Methodsmentioning
confidence: 99%
“…В зарубежной литературе этот критерий носит название 'stone free rate' (SFR) [5,6]. На практике коэффициент эффективности Esfr колеблется в диапазоне 40,0 -95,0% [7].…”
Section: Introductionunclassified